Enhancing or Hindering? AI's Role in Sparking Creativity in Language Teaching: Insights from Private High School EFL Teachers - Akyıldız, Seçil Tümen (Tamer KUTLUCA, 2024)
The integration of artificial intelligence in education presents both opportunities and challenges, particularly in the field of language teaching. This study aims to investigate Turkish EFL teachers' perceptions of AI's role in fostering or hindering creativity in language teaching. Through semi-structured interviews with 10 EFL teachers from private high schools, the research explores the potential benefits and challenges of AI integration. Key findings reveal that AI enhances student engagement, provides personalized learning experiences, and offers timely feedback. However, concerns about insufficient training, technical issues, and over-reliance on AI potentially undermining fundamental skills were also expressed. While AI tools support improvements in language skills and foster creative thinking, there is apprehension about standardization and the risk of diminishing originality. The study underscores the necessity for effective teacher training and a balanced approach to AI integration, ensuring it complements rather than replaces traditional teaching methods. These insights provide valuable guidance for educators, policymakers, and technology developers to optimize AI use in EFL education while fostering a dynamic and creative learning environment. Future research should explore innovative ways to integrate AI into language teaching without compromising creativity.

The integration of artificial intelligence in education presents both opportunities and challenges, particularly in the field of language teaching. This study aims to investigate Turkish EFL teachers' perceptions of AI's role in fostering or hindering creativity in language teaching. Through semi-structured interviews with 10 EFL teachers from private high schools, the research explores the potential benefits and challenges of AI integration. Key findings reveal that AI enhances student engagement, provides personalized learning experiences, and offers timely feedback. However, concerns about insufficient training, technical issues, and over-reliance on AI potentially undermining fundamental skills were also expressed. While AI tools support improvements in language skills and foster creative thinking, there is apprehension about standardization and the risk of diminishing originality. The study underscores the necessity for effective teacher training and a balanced approach to AI integration, ensuring it complements rather than replaces traditional teaching methods. These insights provide valuable guidance for educators, policymakers, and technology developers to optimize AI use in EFL education while fostering a dynamic and creative learning environment. Future research should explore innovative ways to integrate AI into language teaching without compromising creativity.
Enhancing or Hindering? AI's Role in Sparking Creativity in Language Teaching: Insights from Private High School EFL Teachers
Keywords: Curriculum Development in Education; Eğitimde Program Geliştirme